Neuropeptide Y in the amygdala contributes to neuropathic pain-like behaviors in rats via the neuropeptide Y receptor type 2/mitogen-activated protein kinase axis. Issue 4 (1st April 2022) - Yan, Wenhui; Liu, Wuchao; Wu, Junlu; Wu, Lipei; Xuan, Shihai; Wang, Weiwei; Shang, Anquan
ABSTRACT: Neuropeptide Y (NPY) is a highly conserved endogenous peptide in the central and peripheral nervous systems, which has been implicated in nociceptive signaling in neuropathic pain. However, downstream mechanistic actions remain uncharacterized. In this study, we sought to investigate the mechanism of NPY and its receptor NPY2R in the amygdala in rats with neuropathic pain-like behaviors induced by chronic constriction injury (CCI) of the sciatic nerve. The expression of NPY and NPY2R was found to be aberrantly up-regulated in neuropathic pain-related microarray dataset. Further, NPY was found to act on NPY2R in the basolateral amygdala (BLA). As reflected by the decrease in mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) as well as the increase of NPY expression in the amygdala of rats with neuropathic pain-like behaviors, NPY was closely related to the effect of amygdala nerve activity in neuropathic pain. Subsequently, mechanistic investigations indicated that NPY2R activated the MAPK signaling pathway in the amygdala. NPY2R-induced decrease of MWT and TWL were also restored in the presence of MAPK signaling pathway antagonist. Moreover, it was revealed that NPY2R overexpression promoted the viability while inhibiting the apoptosis of microglia. Taken together, NPY in the amygdala interacts with NPY2R to activate the MAPK signaling pathway, thereby promoting the occurrence of neuropathic pain. Graphical Abstract: uf0001